The Influence of Oil Price Volatility and Price Limit in Indonesia Energy Sub-Sector for the Period Before and After Covid-19 - Alexandri, Mohammad Benny; Supriyanto, Supriyanto (International Journal of Energy Economics and Policy, 2021)
This study aims to analyze the determinants of the influence of oil price volatility and price limits on Energy sub-sector companies listed on the Indonesia Stock Exchange in 2018-2021 before and after Covid-19. This study uses the Eviews 10 program as information preparation and the results of irregular influence are selected to see the relationship between the dependent and independent variables which calculates oil price volatility (WTI), price limit (PL), return on assets (ROA), earnings per share (EPS) , and exchange rate (FOREX). The result is that the current proportion, the ratio of Return on Resources (ROA), and Trade Rate (FOREX) do not affect stock returns. Price limit (PL), Earning Per Share (EPS), and World Oil Cost (WTI) affect the return of shares of energy sub-sector companies, namely oil and coal which are listed on the Indonesia Stock Exchange in 2018-2021 period before and after Covid-19. Keywords: Oil Price, Price Limit, Probability, Forex, Covid-19 JEL Classifications: E22, E44, G11, O42, Q47 DOI: https://doi.org/10.32479/ijeep.11557